A Basic Pareto Distribution To Solve The Length Of Stay At Hospital By Using Fuzzy Stochastic Transportation Problem - Bhavana, Pullooru; Priya, Dr. D.Kalpana (Migration Letters, 2023)
In this paper a fuzzy time algorithm is applied using stochastic transportation problem with the aspect of Pareto distribution in the rearrangement of hospital bed and length of long stay at hospital.The LOS at hospital have the major three objectives – reduction of expenses, effectiveness of treatment, and the lack of available beds. The LOS measure is used to make the decisions based on the given objectives because it is dependent on the variations of the losses, determining the number of reassigned in each department’s bed might thus be viewed as stochastically. Computational results with numerical.